2020
DOI: 10.1002/anie.202011887
|View full text |Cite
|
Sign up to set email alerts
|

The Network of Replication, Transcription, and Reverse Transcription of a Synthetic Genetic Cassette

Abstract: Synthetic nucleic acids, with four non‐canonical nucleobases, can function as genetic materials. A comprehensive analysis of PCR amplification, transcription, reverse transcription, and cloning was done to screen for alternative genetic monomers. A small library of six modified nucleobases was selected: the modified 2′‐deoxyribonucleoside (dZTPs) and ribonucleoside (rZTPs) triphosphates of 7‐deaza‐adenine, 5‐chlorouracil, 7‐deaza‐guanine or inosine together with 5‐fluorocytosine or 5‐bromocytosine. The fragmen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

3
14
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
4

Relationship

2
2

Authors

Journals

citations
Cited by 4 publications
(17 citation statements)
references
References 65 publications
3
14
0
Order By: Relevance
“…This might be due to the use of the forcing PCR condition that lowered the DNA polymerase fidelity towards nucleoside misincorporation (e. g., error prone Taq polymerase with elevated concentration of Mg 2+ ions was used) [22] . These results align with our previous reports, [11,12] where 7‐deazaA was identified as the most mutagenic nucleotide among the other modifications. Despite the incorporation of errors in the synthetic gene, the fully functional protein was expressed in a eukaryotic organism from DZA genetic material even when all four nucleotides were substituted to their non‐canonical counterparts.…”
Section: Resultssupporting
confidence: 93%
See 3 more Smart Citations
“…This might be due to the use of the forcing PCR condition that lowered the DNA polymerase fidelity towards nucleoside misincorporation (e. g., error prone Taq polymerase with elevated concentration of Mg 2+ ions was used) [22] . These results align with our previous reports, [11,12] where 7‐deazaA was identified as the most mutagenic nucleotide among the other modifications. Despite the incorporation of errors in the synthetic gene, the fully functional protein was expressed in a eukaryotic organism from DZA genetic material even when all four nucleotides were substituted to their non‐canonical counterparts.…”
Section: Resultssupporting
confidence: 93%
“…Previously, we demonstrated that partially or fully substituted DZA fragments conferring resistance to antibiotic or fluorescent reporter gene could accurately transfer genetic information in E. coli [11,12] . Here, we were questioning whether eukaryotic organisms could read and process the information from the synthetic DZAs as well.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…In the past, there were only several scattered examples 9,10 of polymerase synthesis of DNA containing all-four modified bases and one set of four small base-modified nucleotides (not decorated by functional groups) was used for in vivo chemical morphing of bacteria. 11…”
mentioning
confidence: 99%